Kemampuan Komunikasi Matematika Siswa dalam Pembelajaran - Annisak, Fadillah; Wandini, Rora Rizky (TSAQOFAH, 2024)
Communication is a routine activity of every human interaction between two or more people. Basically, every activity in transferring ideas or ideas from one party to another or between humans or between humans and the natural surroundings and vice versa. Mathematical communication is an important skill in mathematics, namely the ability to describe mathematical ideas in an integrated manner to teachers, friends and others through written and spoken language. The research method used is qualitative research with descriptive analysis through a literature study approach.